Pain chronification: what should a non-pain medicine specialist know?. (3rd July 2018) - Morlion, Bart; Coluzzi, Flaminia; Aldington, Dominic; Kocot-Kepska, Magdalena; Pergolizzi, Joseph; Mangas, Ana Cristina; Ahlbeck, Karsten; Kalso, Eija
Abstract: Objective: Pain is one of the most common reasons for an individual to consult their primary care physician, with most chronic pain being treated in the primary care setting. However, many primary care physicians/non-pain medicine specialists lack enough awareness, education and skills to manage pain patients appropriately, and there is currently no clear, common consensus/formal definition of "pain chronification". Methods: This article, based on an international Change Pain Chronic Advisory Board meeting which was held in Wiesbaden, Germany, in October 2016, provides primary care physicians/non-pain medicine specialists with a narrative overview of pain chronification, including underlying physiological and psychosocial processes, predictive factors for pain chronification, a brief summary of preventive strategies, and the role of primary care physicians and non-pain medicine specialists in the holistic management of pain chronification. Results: Based on currently available evidence, we propose the following consensus-based definition of pain chronification which provides a common framework to raise awareness among non-pain medicine specialists: "Pain chronification describes the process of transient pain progressing into persistent pain; pain processing changes as a result of an imbalance between pain amplification and pain inhibition; genetic, environmental and biopsychosocial factors determine the risk, the degree, and time-course of chronification." Conclusions: Early intervention plays an important role in preventing pain chronification and, as key influencers in the management of patients with acute pain, it is critical that primary care physicians are equipped with the necessary awareness, education and skills to manage pain patients appropriately.